Гепатопротекторные свойства полифенольных веществ экстракта «Дубовый» = Hepatoprotective properties of polyphenols substances of Oak extract - Levitsky, A. P.; Makarenko, O. A.; Khodakov, I. V.; Lukanin, A. S.; Lukanina, M. A. (Journal of Education, Health and Sport, 2017)
Levitsky A. P., Makarenko O. A., Khodakov I. V., Lukanin A. S., Lukanina M. A. Гепатопротекторные свойства полифенольных веществ экстракта «Дубовый» = Hepatoprotective properties of polyphenols substances of Oak extract. Journal of Education, Health and Sport. 2016;6(11):537-547. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.192393 http://ojs.ukw.edu.pl/index.php/johs/article/view/4039 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016. УДК 615.07+615.015+616.98 ГЕПАТОПРОТЕКТОРНЫЕ СВОЙСТВА ПОЛИФЕНОЛЬНЫХ ВЕЩЕСТВ ЭКСТРАКТА «ДУБОВЫЙ» А. П. Левицкий1, О. А. Макаренко1, И. В. Ходаков1, А. С. Луканин2, М. А. Луканина3 1ГУ «Институт стоматологии и челюстно-лицевой хирургии Национальной академии медицинских наук Украины» (г. Одесса) E-mail: flavan@mail.ru 2Лаборатория мониторинга сырьевых ресурсов для виноделия (г. Киев) 3ГП «Государственный центр сертификации и экспертизы сельскохозяйственной продукции Минагрополитики Украины» (г. Киев) Резюме Экстракт «Дубовый» обладает гепатопротекторным действием при токсическом гепатите. Ключевые слова: гепатит, полифенолы дуба, гепатопротектор, ферменты, липиды. HEPATOPROTECTIVE PROPERTIES OF POLYPHENOLS SUBSTANCES OF OAK EXTRACT A. P. Levitsky, O. A. Makarenko, I. V. Khodakov, A. S. Lukanin, M. A. Lukanina 1SE «The Institute of Stomatology and Maxillo-Facial Surgery of the NAMS of Ukraine» (Odessa, Ukraine) flavan@mail.ru 2The Laboratory of monitoring of raw materials for wine-making (Kiev, Ukraine) 3The state of sertification and expertise agriculture products of Ministry of agropolitics (Kiev, Ukraine) Summary Purpose of work: To determine of hepatoprotective properties of oak extract. Materials and methods: The oak extract, wich contained 1,3 % polyphenols, was used. The hepatoprotective properties were determined using rats with hydrazine hepatitis. The oak extract was introduced in dose of 10 ml/kg from the first day of the experiment during 13 days. The liver state was estimated by inflammation indices (elastase, MDA) index of microbe sowing (urease), index of non-specific immunity (lysozyme), index of cholestasis (alkaline phosphotase, AlPh). The liver markers (bilirubine, ALT, AlPh) were determined into serum. The levels of triglycerides and total cholesterine were determined into liver and serum. Results: The oak extract reduced of inflammation indices, the activaties of urease, AlPh into liver and the degree of dysbiosis into liver and serum. The conclusion: The oak extract has hepatoprotective action. Key words: hepatite, polyphenols of oak, hepatoprotectore, enzymes, lipids.